FACTORS ASSOCIATED WITH THE ABILITY TO PERFORM PHYSICAL FITNESS TESTS WITH QCST - Nawawiwetu, Erwin Dyah; Lutfiya, Indah (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: VO2 max measurement method for physical fitness test using QCST method has been widely used. VO2 max measurement is important for workers to determine the appropriate loading. There are several factors related to a person's ability to carry out physical fitness tests, including body posture, pulse, BMI, gender. Purpose: analyze factors related to the ability to conduct tests with the QCST method. Method: This research was analytic observational type which was conducted cross-sectional on 46 respondents taken randomly on 48 third-year D3K3 students in the Faculty of Vocational Studies of Universitas Airlangga. The independent variable consisted of gender, resting pulse rate and BMI. Dependent variable is the ability to complete the QCST test for 3 minutes. The relationship between variables was tested using the Fischer and Chi-square test with a significance of 5%. Result: The results showed that most respondents were unable to complete the QCST test for 3 minutes. There is no relationship between the ability to perform the QCST test with gender (p=0,365); resting pulse (p = 0,351) and BMI (p =0,187). Conclusion: QCST test for 3 minutes is too heavy for respondents. It is necessary to modify the QCST test that is appropriate for Indonesians.